2017
DOI: 10.1038/s41371-017-0028-8
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and prevalence of high blood pressure among Chinese adults

Abstract: Epidemiological studies demonstrated that Helicobacter pylori (H. pylori) infection was associated with cardiovascular disease and its risk factors. However, the association between H. pylori infection and hypertension remained unclear. The aim of this study was to investigate the association between H. pylori infection and prevalence of hypertension among Chinese adults. We performed a cross-sectional study of 5246 adult participants who were recruited from a health manage center. All participants underwent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 35 publications
3
41
1
3
Order By: Relevance
“…A large‐scale, community‐based study in an Iranian population indicated that H pylori infection showed a significant association with hypertension by testing for immunoglobulin G (IgG) antibodies 17 . The results of a cross‐sectional study performed by Wan et al 9 were consistent with our findings. In contrast with the results of our study, Hartog et al 18 tested for H pylori using antibodies among 440 Dutch, 320 Turkish, and 272 Moroccan participants and found that H pylori infection was weakly associated with hypertension but was not statistically significant.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A large‐scale, community‐based study in an Iranian population indicated that H pylori infection showed a significant association with hypertension by testing for immunoglobulin G (IgG) antibodies 17 . The results of a cross‐sectional study performed by Wan et al 9 were consistent with our findings. In contrast with the results of our study, Hartog et al 18 tested for H pylori using antibodies among 440 Dutch, 320 Turkish, and 272 Moroccan participants and found that H pylori infection was weakly associated with hypertension but was not statistically significant.…”
Section: Discussionsupporting
confidence: 90%
“…However, we found that H pylori infection was related to a higher DBP but not SBP, PP, and MAP. A cross‐sectional study indicated that H pylori infection was positively associated with DBP but not SBP 9 . Meanwhile, Migneco et al 13 demonstrated a significant decrease in DBP after H pylori eradication in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little has been done to identify the association of osteoclast differentiation and neurotrophin signaling pathway with hypertension. There were also three ways participating in infection, such as toxoplasmosis [ 31 ], pertussis [ 32 ], epithelial cell signaling in Helicobacter pylori infection [ 33 ], which have been proved to be related with hypertension, while pathways involving hepatitis B and tuberculosis have not been proved to be associated with hypertension. However, mechanisms of those pathways interacted with hypertension remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, enrolling 5246 Chinese patients, reported a 32.6% prevalence of H pylori infection using UBT, and the presence of a concomitant blood hypertension in 955. H pylori infection was significantly associated with hypertension, even after adjusting the data for possible confounders, such as age, sex, and other cardiovascular risk factors …”
Section: Cardiovascular Diseasesmentioning
confidence: 98%